2010
DOI: 10.1111/j.1365-2605.2009.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in subjects with Klinefelter’s syndrome

Abstract: While the association of Klinefelter's Syndrome (KS) with infertility is well-known, very few investigations have evaluated the prevalence of sexual dysfunction in KS. The aim of the present study was to systematically analyse the prevalence of KS in a consecutive series of adult male patients consulting for sexual problems and to investigate its specific correlates. Among a consecutive series of 1386 men (mean age 48.9 +/- 12.7 years old), 23 (1.7%) subjects with KS were found. Patients with KS were younger a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 35 publications
3
73
0
Order By: Relevance
“…Discordant data on sexual desire, and lower coital and orgasm frequency have been published. Besides erectile dysfunction, hypoactive sexual desire was the most frequent complaint in men with KS attending an outpatient clinic for sexual problems (85). In this study, sexual problems were, however, not more frequent when compared with a testosterone-matched control group, confirming that the low sexual desire in KS is not only related to the testosterone deficiency.…”
Section: Sexual Dysfunctionsupporting
confidence: 49%
“…Discordant data on sexual desire, and lower coital and orgasm frequency have been published. Besides erectile dysfunction, hypoactive sexual desire was the most frequent complaint in men with KS attending an outpatient clinic for sexual problems (85). In this study, sexual problems were, however, not more frequent when compared with a testosterone-matched control group, confirming that the low sexual desire in KS is not only related to the testosterone deficiency.…”
Section: Sexual Dysfunctionsupporting
confidence: 49%
“…Others have shown a prevalence of 30-80% in men with type 2 diabetes. 9,22 This study also revealed that FBG contributes to lowering TT levels in men with type The association between glycemia and reduced TT concentrations may be an effect of glycemia on the testicular microvasculature. Thus, glycemia alters Ledig cell function, directly causing primary hypogonadism.…”
mentioning
confidence: 83%
“…There was not a significant difference in the frequency of sexual function disturbances between the patients with KS and the control group. In the study by Corona et al (2010), 22.7% of KS patients reported severe ED, 60.9% hypoactive sexual desire (HSD), 9.5% premature ejaculation and 9.5% delayed ejaculation. However, adjusting for age, in a multiple logistic regression model, only a higher risk for HSD continued to be observed in KS subjects (Corona et al, 2010).…”
Section: Non-obstructive Azoospermiamentioning
confidence: 98%
“…In the study by Corona et al (2010), 22.7% of KS patients reported severe ED, 60.9% hypoactive sexual desire (HSD), 9.5% premature ejaculation and 9.5% delayed ejaculation. However, adjusting for age, in a multiple logistic regression model, only a higher risk for HSD continued to be observed in KS subjects (Corona et al, 2010). The authors concluded that HSD, eventually present in the KS subjects, is more related to the testosterone deficiency than to the genetic abnormality.…”
Section: Non-obstructive Azoospermiamentioning
confidence: 98%